HYPERACCUMULATOR PLANTS FOR PHYTOREMEDIATION OF SOIL CONTAMINATED WITH HEAVY METALS - Yelikbayev, B.K.; C. Pagano, Marcela; Jamalova, G.A. (Scientific Journal of Pedagogy and Economics, 2020)
Environmental pollution, including pollution of urban soils by heavy metals causes serious environmental concern around the world. Heavy metals accumulate relatively quickly in soil but their removal rate is very slow. Hyperaccumulator plants help cleanse the environment from heavy metals. Phytoremediation is cleansing of soils contaminated with heavy metals, using plants that accumulate significant amounts of metals. An important environmental problem in large industrial cities is pollution by toxic compounds, including heavy metals. Due to the potential toxicity and high resistance of metals, soils contaminated with these elements are an environmental problem that requires effective and affordable solution. In soils heavy metals are in varying degrees of accessibility to plants. Water-soluble forms of heavy metals, as a rule, are presented in the form of various salts and organic complex compounds. Phytoremediation of urban soils from heavy metals is an important environmental challenge. Among the wild species, a special group of heavy metal hyperaccumulator plants is highlighted. Some of the land plants that can accumulate abnormally high levels of potentially toxic trace elements are known as “hyperaccumulators” and their number includes about 500 taxa. Phytoremediation is much more environmentally friendly and cheaper than other techniques, so recently it has received widespread use in various countries.